Factores de riesgo asociados a osteoporosis en mujeres mayores de 50 años atendidas en el Hospital Essalud Tarapoto, agosto 2015 a marzo 2016 - Arevalo Del Aguila, Diana Karolly (2017)
Objective: To determine the risk factors associated with osteoporosis in women older than 50 years old treated at EsSalud Tarapoto Hospital, August 2015 - March 2016. Methodology: An analytical, observational, retrospective, cross-sectional study of cases and control was performed, between August 2015 and March 2016. The sample consisted of 90 clinical histories in each group (with and without osteoporosis), selected through simple random sampling. The associations were considered significant if the possibility of error is less than 5% (p <0.05) and to identify the association between risk factors and osteoporosis; we calculated the odds ratio (OR) and its corresponding 95% confidence interval. Results: Risk factors with a significant association to develop osteoporosis were the postmenopausal state with an OR of 16.2 (95% CI, 20.09-125.65, p = 0.0218), smoking with OR of 8.2 (95% CI, 2.03 -8.87, p = 0.0347), sedentary lifestyle with OR of 3.9 (95% CI, 2.07-7.36, p = 0.0371), and decreased sun exposure with OR of 5.2 (95% CI 2.02-12.84, p = 0.0221). Conclusion: Postmenopausal state, sedentary lifestyle, smoking, and decreased sun exposure are important risk factors for developing osteoporosis